Translation shift analysis of thematic structure in printed political news reports of Indonesian local newspaper - Indah Arti Fisilla; Ernie Diyahkusumaning Ayu Imperiani (Passage, 2020)
This study aims to investigate translation shifts of textual metafunction in printed news reports of the Pikiran Rakyat newspaper. This study used a descriptive-qualitative method to investigate the consistency of the alignment from the news writers in translating articles. The data were taken from five printed political news articles along with its translation published from 19th March to 21st March, 2018. The data were analyzed by using Hallidayan framework of Systemic Functional Grammar and Newmark’s Translation Shift. The findings show that in terms of thematic structures, there were found 29.1% theme shifts of 79 clauses. It is found that the translators are manage to maintain the objectivity in the news reports. Further, this study discovers that the combination of structure and unit shift recurred frequently for 49.5% in translation. Then, it is followed by unit shift 21.5%, structure shift 10.2%, and the combination of class and unit shift 8.7%. The translation shift from the data shows that almost 50% of structure and unit shift are used frequently. It is concluded that Pikiran Rakyat tried to translate the contextual meaning in the source text, both in aspects of language and its content, so that readers can accept and agree with what being delivered. Keywords: Media, newspaper, translation shifts, alignment, political news, structures, thematic structures.